MEASUREMENT OF THE SURFACE TOPOGRAPHY CHANGE ON A BOUNDARY LUBRICATED RECIPROCATING SLIDING CONTACT - Jamari, Jamari (ROTASI, 2008)
This paper presents experiments to study the change of the surface topography on a boundary lubricated reciprocating sliding contact system. A Â Micromap 512 optical profilometer is employed for measuring surface characteristics. The change of the surface topography before and after the experiment is determined in detail and accurate (microscopically) by the Matching and Stitching method.Â  Plot of the profile of the surface roughness for a certain number of running-in cycles were presented in a figure for before, after and difference, so that analysis of the surface topography change can be accurately performed